2023
DOI: 10.3390/healthcare11060780
|View full text |Cite
|
Sign up to set email alerts
|

How Advanced Practice Nurses Can Be Better Managed in Hospitals: A Multi-Case Study

Abstract: The labor markets for care professionals are a perennial topic of discussion. Advanced practice nurses (APN), as an advanced role in nursing, arose to solve the shortage of primary health care professionals. Prior research has advanced several areas of exploration for APNs’ training or employing methods in Chinese hospitals. However, this leaves a key imperative unexplored: the management strategy of APNs in hospitals. The present study seeks to explore the management strategy of APNs in Chinese hospitals. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…On the other hand, it is noteworthy that leadership is the primary competency dimension among intermediate-level CNSs, standing out above all other roles. Leadership is essential for clinical practice, especially for teamwork collaboration, and multidisciplinary collaboration can further provide better clinical care to suit patients' needs and contribute to clinical research promotion (39). Only through effective management can the full value of resources be realized, ultimately leading to the greatest professional development and clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is noteworthy that leadership is the primary competency dimension among intermediate-level CNSs, standing out above all other roles. Leadership is essential for clinical practice, especially for teamwork collaboration, and multidisciplinary collaboration can further provide better clinical care to suit patients' needs and contribute to clinical research promotion (39). Only through effective management can the full value of resources be realized, ultimately leading to the greatest professional development and clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study from Poland showed that besides financial stability, the flow of information was a significant predictor of WHO-5, PHQ-9, and ISI scores [45]. According to Wan and Xia, "It is crucial to accumulate, bind, and effectively utilize human resources" [46]. However, in a recent study, "occupational stress was more closely related to perceptions of lack of distributive justice than to perceptions of procedural, informational, and interpersonal justice" [47].…”
Section: Information Channelsmentioning
confidence: 99%
“…First, the long queuing times for seeing a doctor is a key problem in the pediatric outpatient medical service of Xinhua Hospital. According to the data released by Xinhua Hospital (as of September 2021), the average daily outpatient volume of pediatric outpatient clinics is around 400, and the average monthly outpatient volume is about 10,000 [88,89]. Especially in some specific periods, the number of patients increased dramatically, such as during the summer vacation and winter vacation [63,81,[90][91][92][93][94][95].…”
Section: Current Situation Of Pediatric Outpatient Clinic In Shanghaf...mentioning
confidence: 99%
“…Sustainability 2023, 15, x FOR PEER REVIEW 5 of 47 pediatric outpatient clinics is around 400, and the average monthly outpatient volume is about 10,000 [88,89]. Especially in some specific periods, the number of patients increased dramatically, such as during the summer vacation and winter vacation [63,81,[90][91][92][93][94][95].…”
Section: Current Situation Of Pediatric Outpatient Clinic In Shanghaf...mentioning
confidence: 99%